A Pilot Study of Baseline Spatial Genomic Heterogeneity in Primary Gastric Cancers Using Multi-Region Endoscopic Sampling - Chao, Joseph; Lee, Jeeyun; Kim, Kyung; Kang, So Young; Lee, Taehyang; Kim, Kyoung-Mee; Kim, Seung Tae; Klempner, Samuel J.; Lee, Hyuk (Frontiers in Oncology, 2020)
Intertumoral heterogeneity among actionable biomarkers including ERBB2, FGFR2 and EGFR has been observed to occur under therapeutic pressure in advanced gastric cancer. However, baseline intratumoral heterogeneity at diagnosis is understudied and may impact clinical outcomes. We sought to explore intratumoral heterogeneity in primary advanced gastric cancers via DNA sequencing from multi-region endoscopic sampling at diagnosis. Patients with newly diagnosed advanced gastric adenocarcinoma underwent endoscopic mapping and pre-determined 8-sector biopsy of the primary tumor with concurrent plasma cfDNA sampling. Biopsy samples were subjected to targeted next generation sequencing and plasma cfDNA was analyzed via a 28-gene cfDNA assay. Expectedly, we observed that the majority of genetic alterations were shared among multi-sector biopsies within the same gastric primary tumor. However, all samples contained private subclonal alterations between biopsy sectors, including actionable alterations in GNAS and STK11. Cell free DNA analyses also exhibited both shared and non-shared alterations between mutations detected in cfDNA and tumor tissue biopsies confirming baseline intertumoral heterogeneity. This is the first dataset to confirm baseline intratumoral heterogeneity and confirms that multi-sector endoscopic biopsy is feasible and capable of capturing intratumoral heterogeneity among relevant genomic alterations in gastric cancer. Both multi-sector endoscopic biopsies and cfDNA analyses are complementary in capturing the diverse mutational landscape at disease presentation.